Voicing "Phono-Indexicals": On the Politics of Vocalic Variation in Metasemiosis - Taylor, Chris (Recherches sémiotiques / Semiotic Inquiry, 2012)
Research on reflexivity in communication has shown that speakers leverage a range of semiotic strategies to segment and characterize linguistic variability. My work explores how entextualization and intertextuality play key roles in dialogically managing interpretations of sociophonetic variability (cf. Schilling-Estes 1998). I examine how speakers “voice” and comment on vocalic variation by employing interrelated modes of metapragmatic typification, including eye-dialect spelling, (explicit) metapragmatic discourse, constructed dialogue (Tannen 1989), and parodic double-voicing (Bakhtin 1981; Sclafani 2009). These strategies prove indispensable to the metapragmatic framing of phono-indexicals because most phonetic features in speech become objects of metasemiotic activity by virtue of their realization in specific words and salient texts, which in turn serve as sign vehicles for vocalic variables and other “semiotic hitchhikers” (Mendoza-Denton 2011). Accordingly, our capacity to reflexively model the pragmatics of sociophonotic variables derives in large part from our ability to segment and evaluate the more metalinguistically-available structures in which these phono-indexicals occur.The case of /aw/ monophthongization in the speech of many young black women and men in Houston, Texas supports this position. Drawing on five years of ethnographic research at a public radio station in Houston, I consider how this pronunciation feature becomes tethered indexically to contested formulations of authenticity and indigineity by virtue of its occurrence in a locally-salient idiom, COMIN’ DINE ([kʌmn dãːn] “coming down”). This idiom has become an enregistered emblem of a street-savvy “gangsta” persona in the popular music of Houston-based hip hop cultures. In this music, recontextualized across globally-circulating media, the expression of COMIN’ DINE puts sociophonetic variation on display, rendering it available for metasemiotic negotiation through “Bakhtinian voicing” (Jaffe 2009).